Pre-treatment of petroleum refinery wastewater by coagulation and flocculation using mixed coagulant: Optimization of process parameters using response surface methodology (RSM) - Singh, B.; Kumar, P. (Elsevier Ltd, 2020)
The present work reports the efficacy of three coagulants CuSO4, FeCl3 and CuSO4+FeCl3 (both salt mixed in 1:1 ratio (v/v)) for treatment of wastewater from effluent treatment plant of petroleum refinery using coagulation and flocculation process. The independent parameters such as pH and dosage of coagulants were optimized using response surface methodology with central composite design technique considering final pH, reduction in COD, turbidity, TDS and color as dependent variables. The statistical fitness of developed model was checked using ANOVA. A second order quadratic model (R2 > 95 %) was best fitted to develop the relation between independent and dependent variables. Charge neutralization, sweep flocculation, adsorption and formation of tribasic copper chloride (TBCC) were mainly responsible for coagulation and flocculation processes. Results showed that mixed coagulant CuSO4+FeCl3 delivered better result than CuSO4 and FeCl3 individually. CuSO4+FeCl3 along with adsorption and sweep flocculation, forms tribasic copper chloride (TBCC) as a proceeding intermediate in the pH range 5−7. The TBCC formation enhanced the flocculation by destabilizing colloidal and suspended particles due to its catalytic, decolorizing and octahedral structural properties. Maximum reduction in COD (76.77 %), turbidity (89.47 %), TDS (94.16 %) and color (95.29 %) was observed at pH 7.12 and 0.20 g/L dosage of CuSO4+FeCl3 coagulant. The final pH of solution at optimum condition for all three coagulants was under the disposal limits. Further, the flocs formed are characterized using XPS, SEM and EDX analyses to reveal the formation of TBCC as intermediate during the process. © 2020 Elsevier Ltd
Keywords: Petroleum refinery wastewater; Pre-Treatment; Coagulation-Flocculation; Response surface methodology; Tribasic copper chloride